The Development of The Physics Module with Scientific Process Skill Approach (SPS) to Uniform Circular Motion Learning Materials 10th Grade at MAN 1 Magelang District - Rachmayani, Arimbi; Widayanti (Proceeding International Conference on Science and Engineering, 2021)
Abstract. The purpose of scientific research is to develop a module with a skills process approach to enhance cognitive, affective, and psychomotor concurrently. This study also aims to see the quality of the modules that have been developed. The method used is a researchbased development or development method with the 4D model developed by Thiagarajan, Shivasailam, et.al. The physics module is developed using a science process skills approach. The instruments used in this study were questionnaires, observation sheets, validation sheets, and sheets. The analysis used in the validation sheet is descriptive. Assessment of the quality and response of students to the physics module using a scale of 4 made in the form of a checklist. The results showed 1) the physics module has been developed with a science process skills approach. 2) the physics module with the science process skill approach according to the criteria is very good seen from the results made by material experts with an average of 3.55; a media expert with an average of 3.36, and a physics teacher with a score of 3.52. Also, the results of the limited test student response state that this physics module agrees to be used.